Factors that influence on sexual behavior in Nahua women in Puebla, Mexico - Nava-Navarro, Vianet; Báez-Hernández, Francisco Javier; Morales-Nieto, Arelia; García-Madrid, Guillermina; Flores-Arias, María Luisa (Acta Universitaria, 2019)
Indigenous women (IW) are a vulnerable group that experiences multiple forms of discrimination and invisibility. The aim of this study was to determine whether the age of the beginning of sexual life, schooling, knowledge about HIV/AIDS, and other sexually transmitted infections, benefits, barriers and perceived self-efficacy for condom use as well as partner violence influence sexual behavior in indigenous women. This is a descriptive, cross-correlation study that was carried out in 386 indigenous women. The sampling was probabilistic through random numbers of the population census of the Nahua community. Schooling (R2 = 0.02, F[386] = 6.140, p < 0.014), perceived self-efficacy for condom use (R2 = 0.13, F[386] = 5.167, p < 0.024), and partner violence (R2 = 0.02, F[386] = 2.55, p < 0.039) influence the sexual behavior of indigenous women. It is necessary to continue a deeper review in other factors that may be associated with sexual behavior in IW, considering these findings to design strategic and appropriate programs.